2019
DOI: 10.1073/pnas.1901086116
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric base-pair opening drives helicase unwinding dynamics

Abstract: The opening of a Watson–Crick double helix is required for crucial cellular processes, including replication, repair, and transcription. It has long been assumed that RNA or DNA base pairs are broken by the concerted symmetric movement of complementary nucleobases. By analyzing thousands of base-pair opening and closing events from molecular simulations, here, we uncover a systematic stepwise process driven by the asymmetric flipping-out probability of paired nucleobases. We demonstrate experimentally that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…The xrRNA structure was represented with SMOG. The model retains the full atomistic details and has been validated for various molecular systems, including nucleic acids [23][24][25][26]. SMOG employs a native-centric force field that allows us to highlight structure-dependent properties while filtering out details more related to sequence or specific RNA-protein interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The xrRNA structure was represented with SMOG. The model retains the full atomistic details and has been validated for various molecular systems, including nucleic acids [23][24][25][26]. SMOG employs a native-centric force field that allows us to highlight structure-dependent properties while filtering out details more related to sequence or specific RNA-protein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute temperature was calibrated similarly to ref. [25] by matching the experimental condition that mechanical unfolding of RNA helices [44,45] occur at about 15pN at 300K, see Supplementary Methods and Supplementary Table 1.…”
Section: Zika Xrrna and System Setupmentioning
confidence: 99%
“…The latter fact also rules out the helical asymmetry of nucleic acids, see e.g., refs. 23 , 34 , as a cause for xrRNAs directional resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute temperature was calibrated similarly to ref. 23 by matching the experimental condition that mechanical unfolding of RNA helices 42 , 43 occur at about 15 pN at 300 K, see Supplementary Methods and Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…As an initial test, we used delta-Melt to measure the conformational penalty associated with opening Watson-Crick A-T base pairs (bps) in DNA. Base opening is the elementary step that drives melting and annealing of nucleic acids, and their unwinding by helicases 6 . Measurements of imino proton exchange rates 7 have shown that Watson-Crick A-T bps transiently open to form exceptionally low-populated (population~0.001%) and short-lived (lifetime~0.1 s) conformations (Fig.…”
Section: Main Textmentioning
confidence: 99%